Physical fractions of organic matter in an Oxisol cultivated with sugarcane in the state of Rio Grande do Sul, Brazil - Kunde, Roberta Jeske; Lima, Cláudia Liane Rodrigues de; Silva, Sérgio Delmar dos Anjos; Pillon, Clenio Nailto (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the physical fractions of soil organic matter (SOM) and the carbon management index (CMI) after different periods of soil tillage for sugarcane implantation. The study was carried out in a clayey Oxisol after 1, 3, and 5 years from soil tillage for crop plantation, with burning of the straw and manual cutting for harvest. As a reference, the soil of a native forest adjacent to the studied area was used. Soil samples were collected at the 0.00–0.05, 0.05–0.10, and 0.10–0.20-m soil layers, in order to quantify the CMI, as well as total organic C, particulated C, C associated with minerals, and C in the free light, occluded light, and heavy fractions of SOM. Soil tillage associated with previous burning of straw reduced the input of fresh organic matter to the soil and accelerated the decomposition of the SOM labile compartment, negatively affecting the stocks of soil physical fractions. The highest C proportions were observed in the fraction associated with minerals. The SOM density fractions were more sensible to detect changes in the stocks, lability, and the CMI, in the different crop implantation times. The cultivated areas had CMI lower than 100, which indicates the negative impacts of cropping on the stocks of organic matter and on soil physical quality.